WEBVTT
00:00:02.440 --> 00:00:05.950
Simplify the cube root of 18 plus the cube root of 18.
00:00:07.150 --> 00:00:24.590
Whenever youβre trying to simplify a cube root, it actually works in the same way as when weβre trying to simplify a surd because if we had π cube root of π₯ plus π the cube root of π₯, then the result would just be π plus π multiplied by the cube root of π₯.
00:00:25.880 --> 00:00:36.180
So then if we apply this to our expression, we can actually think of it as being a one before our cube root of 18 because itβs just a singular cube root 18.
00:00:36.210 --> 00:00:40.360
So we have one cube root of 18 plus one cube root of 18.
00:00:41.610 --> 00:00:45.650
So therefore, this equals to one plus one cube root of 18.
00:00:46.570 --> 00:00:49.930
So therefore, we can say that because one plus one is two.
00:00:50.250 --> 00:00:57.440
Then, cube root of 18 plus the cube root of 18 fully simplified just equal to two cube root of 18.